Ionization Study of Isomeric Molecules in Strong-field Laser Pulses - Zigo, S.; Le, Anh Thu; Timilsina, P.; Trallero, Carlos (My University, 2017)
Through the use of the technique of time-of-flight mass spectroscopy, we obtain strong-field ionization yields for randomly oriented 1,2-dichloroethylene (1,2-DCE) (C2H2Cl2) and 2-butene (C4H8). We are interested in studying the effect of conformal structure in strong-field ionization and, in particular, the role of molecular polarity. That is, we can perform strong-field ionization studies in polar vs non-polar molecules that have the same chemical composition. We report our findings through the ionization yields and the ratio (trans/cis) of each stereoisomer pair as a function of intensity.
Citation: Zigo, S., Le, A. T., Timilsina, P., & Trallero-Herrero, C. A. (2017). Ionization Study of Isomeric Molecules in Strong-field Laser Pulses. Scientific Reports, 7, 8. doi:10.1038/srep42149
Keywords: Multiphoton Ionization; Tunneling Ionization; Harmonic-Generation; Cross-Section; Atoms; Dynamics